MicroRNAs and STAT Interplay - Kohanbash, Gary (2011)
MicroRNA (miR) are emerging as important gene expression regulators often involved in a variety of pathogenesis such as cancers and autoimmunity. Signal Transducers and Activators of Transcription (STAT) proteins are the principle signaling proteins for many cytokines and growth factors, thereby play a critical role in regulating immune cell homeostasis, differentiation and cellular functions. In this review, we discuss recent advances in the field demonstrating active interactions between STATs and miRs, with our primary focus on the promotion and inhibition of immune cells and cancer. Additionally, we review the reciprocal regulations between STATs and miR, and discuss how we can use this knowledge in the context of diseases. For example, recent findings related to STAT1 and miR-155 support the presence of a positive feedback loop of miR-155 and STAT1 in response to inflammatory signals or infection. STAT3 is known to play critical roles in tumorigenesis and cancer-induced immunosuppression. There is a growing body of evidence demonstrating that STAT3 directly activates miR-21, one of miRs that promote cancer cell survival and proliferation. While some miRs directly regulate STATs, there are findings demonstrating indirect STAT regulation by miRs also mediate important biological mechanisms. Therefore, further research is warranted to elucidate significant contributions made by direct and indirect miR-STAT mechanisms. As we learn more about miR pathways, we gain the opportunity to manipulate them in cancer cells to slow down growth or increase their susceptibility anti-tumor immunity.